Upaya Penurunan Nyeri Pada Pasien Dengan Post Appendiktomi - PUTRI NUR CAHYATI, OKTAVIA; , Fahrun Nur Rosyid, S.Kep., Ns., M.Kes (2017)
Appendicitis is the inflammation of the intestine due to narrowing or blockage of the lumen should get treatment at the beginning of such an operation that is not severe, the impact of the operation will appear pain in the abdomen scar. The author describes efforts to reduce pain and provide nursing care of acute pain. The method used is descriptive case study approach used way to get to the services provided is induvidual, holistic, effective and efficient consisting assessment, diagnosis, intervention, implementation and evaluation of nursing. Nursing action 3x24 hours in patients post apendiktomi with acute pain, nursing actions do is teach relaxation techniques deep breath to inhale with the patient close my eyes and breathe through your nose slowly and pull / exhale through the mouth regularly dn slowly, to reduce pain perceived, deep breathing techniques intended to reduce pain and muscle tension or merileksasikan. Acute pain issues resolved partially, thus requiring further support and cooperation with other medical teams.